Shared contexts, shared background, shared values – Homophily in the Finnish parliament members’ social networks on Twitter - Ilkka Koiranen; Aki Koivula; Teo Keipi; Arttu Saarinen (Pergamon Press, 2022)
While Twitter has become an essential part of daily politics across Western countries, little research has focused on origins of politicians’ social circles on social media. This paper contributes to how structural, ideological and contextual factors affect tie formation between parliamentarians’ Twitter networks. The study focuses on Finland, where over 80 percent of parliamentarians are using the platform. For empirical analysis, we first extracted parliamentarians’ followee network connections from their Twitter accounts (36 294 nodes and 113 108 edges) and combined it with data from a national voting advice application, which includes information regarding parliamentarians' societal position and opinions regarding social, cultural and economic issues. According to the explanatory analysis, we found that connections between parliamentarians and the share of mutual followees are clearly based on matching values, similar background and shared contextual factors. Additionally, we found that shared context had strong confounding effects on the function of value homophily in relations and shared networks between Finnish parliamentarians.